INNOVATIVE MANAGEMENT MODEL IN HIGHER EDUCATION - Umida Sabirova; Mavluda Kabirova (Zeta Repository, 2023)
Improving the professional skills of pedagogical personnel and improving the quality of students’ education largely depends on the effectiveness of the methodological work management process. The model developed by the authors brings methodological work to a high, innovative level, which ultimately has a significant impact not only on the effectiveness of improving the qualifications of pedagogical personnel, but also on improving the quality of the educational process in general.